2016
DOI: 10.21608/ijicis.2016.10012
|View full text |Cite
|
Sign up to set email alerts
|

Video Steganography Using Least Significant Bit in Frequency Domain

Abstract: Video steganography is a technique to hide different types of files (secret massages) into a carrying video file. Video files contain a collection of images (frames) and sounds, so most of techniques that apply on images and audio files can be applied to video files also. The large amount of data that can be hidden inside the video and the fact that it is a moving stream of images and sounds gives the cover video files great advantages. In this paper, we present a proposed video steganography algorithm in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Experimental results showed that the stego-video had a good PSNR value and the algorithm was highly secured with good visual quality. Ibrahim et al [24] proposed combining spatial and frequency domain techniques to conceal a secret message in a video series. The algorithm used DCT and LSB techniques to hide the binary form of the secret message.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that the stego-video had a good PSNR value and the algorithm was highly secured with good visual quality. Ibrahim et al [24] proposed combining spatial and frequency domain techniques to conceal a secret message in a video series. The algorithm used DCT and LSB techniques to hide the binary form of the secret message.…”
Section: Introductionmentioning
confidence: 99%